1957
DOI: 10.1083/jcb.3.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Differentiation in the Kidneys of Newborn Mice Studied With the Electron Microscope

Abstract: Renal structure and function are incompletely developed at birth in a number of mammals, including the rat and man. Functional immaturity manifests itself as an inability on the part of the kidney to vary the volume and concentration of the urine (McCance, 1948). I n the rat, renal function matures during the first few weeks after birth (Falk, 1955). Detailed studies of the structural changes in kidneys of newborn animals have been confined largely to the rat.During the first few weeks after birth, the rat kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
0
5

Year Published

1959
1959
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 364 publications
(136 citation statements)
references
References 31 publications
3
128
0
5
Order By: Relevance
“…Although the presence of mitochondria in lysosomes or vacuoles was first reported in 1957 in mammalian cells (22) and in 1992 in yeast (23), the physiological relevance of mitochondrial degradation by autophagy has been unclear. Very recently, in mammalian cells, several studies have suggested that PINK1/ parkin-dependent mitophagy selectively degrades depolarized mitochondria (12,18,19), implying that mitophagy contributes to mitochondrial quality control.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of mitochondria in lysosomes or vacuoles was first reported in 1957 in mammalian cells (22) and in 1992 in yeast (23), the physiological relevance of mitochondrial degradation by autophagy has been unclear. Very recently, in mammalian cells, several studies have suggested that PINK1/ parkin-dependent mitophagy selectively degrades depolarized mitochondria (12,18,19), implying that mitophagy contributes to mitochondrial quality control.…”
Section: Discussionmentioning
confidence: 99%
“…Excess membrane derived from the fusion and dehydration of vacuoles might be the source of the complex arrays of parallel membranes found associated with these inclusions. The combination of a microvillous cell border, subcuticular tubules, apical vacuoles, and dense inclusions is characteristic not only of intestinal cells in suckling animals, but of the visceral epithelium of the mammalian yolk sac (Dempsey, 1953) and the proximal tubular epithelium of the kidney (Rhodin, 1954;Clark, 1957). Both the yolk sac and the proximal tubular epithelium ingest vital dyes and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, entire mitochondrial organelles were often observed in yeast vacuoles and mammalian lysosomes in electron microscopy studies. 10,11 Bulk degradation of cellular contents occurs through a regulated process called autophagy (reviewed elsewhere in this issue); however, a selective form of autophagy, termed mitophagy, is chiefly responsible for elimination of damaged or superfluous mitochondria. In this process, mitochondria are sequestered in doublemembrane vesicles and delivered to lysosomes for hydrolytic degradation.…”
Section: Open Questionsmentioning
confidence: 99%